2017
DOI: 10.1016/j.eurpsy.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control and reward/loss processing in Internet gaming disorder: Results from a comparison with recreational Internet game-users

Abstract: Although playing of Internet games may lead to Internet gaming disorder (IGD), most game-users do not develop problems and only a relatively small subset experiences IGD. Game playing may have positive health associations, whereas IGD has been repeatedly associated with negative health measures, and it is thus important to understand differences between individuals with IGD, recreational (non-problematic) game use (RGU) and non-/low-frequency game use (NLFGU). Individuals with IGD have shown differences in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 68 publications
6
60
0
1
Order By: Relevance
“…Studies did not generally report symptom duration, so the current analysis cannot evaluate the extent to which cognitive problems may pre-date symptoms (perhaps reflecting vulnerability) as opposed to arising because of chronic engagement with internet-related activities. A longitudinal (3-months) exposure of smartphone-naive young adults to heavy smartphone use found it resulted in performance decrease in arithmetic accuracy and increase in concern for appropriateness (a measure of tendencies 26 Dong et al (2010) 27 Kim et al (2017) 28 Ko et al (2014) 29 Littel et al (2012) 30 Liu et al (2004) 31 Luijten et al (2015) 32 Metcalf & Pammer (2014) 33 Sun et al (2009) 34 Yao et al (2015) 35 Zhou et al (2010) 36 Zhou et al (2016) 37 Zhou et al (2014) 38 Chamberlain et al (2017) 20 Choi et al (2013) 39 Choi et al (2014) 40 Li et al (2016) 41 Lim et al (2016) 42 Choi et al (2014) 44 Dong et al (2011) 45 Dong et al (2014) 46 Dong et al (2013) 47 Dong et al (2013) 48 Dong et al (2017) 49 Dong et al (2013) 50 Dong et al (2012) 51 Lim et al (2016) 42 Luijen et al (2015) 32 Wang et al (2015) 52 Xing et al (2014) 53 Yao et al (2015) 35 Yuan et al (2016) 54 Yuan et al (2016) 55 Chammberlain et al (2017) 20 Lorenz et al (2012) 56 Metcalf & Pammer (2014) 33 Pawlikowski & Brand (2011) 57 Qi et al (2015) 58 Sun et al (2009)…”
Section: Age and Symptom Durationmentioning
confidence: 99%
“…Studies did not generally report symptom duration, so the current analysis cannot evaluate the extent to which cognitive problems may pre-date symptoms (perhaps reflecting vulnerability) as opposed to arising because of chronic engagement with internet-related activities. A longitudinal (3-months) exposure of smartphone-naive young adults to heavy smartphone use found it resulted in performance decrease in arithmetic accuracy and increase in concern for appropriateness (a measure of tendencies 26 Dong et al (2010) 27 Kim et al (2017) 28 Ko et al (2014) 29 Littel et al (2012) 30 Liu et al (2004) 31 Luijten et al (2015) 32 Metcalf & Pammer (2014) 33 Sun et al (2009) 34 Yao et al (2015) 35 Zhou et al (2010) 36 Zhou et al (2016) 37 Zhou et al (2014) 38 Chamberlain et al (2017) 20 Choi et al (2013) 39 Choi et al (2014) 40 Li et al (2016) 41 Lim et al (2016) 42 Choi et al (2014) 44 Dong et al (2011) 45 Dong et al (2014) 46 Dong et al (2013) 47 Dong et al (2013) 48 Dong et al (2017) 49 Dong et al (2013) 50 Dong et al (2012) 51 Lim et al (2016) 42 Luijen et al (2015) 32 Wang et al (2015) 52 Xing et al (2014) 53 Yao et al (2015) 35 Yuan et al (2016) 54 Yuan et al (2016) 55 Chammberlain et al (2017) 20 Lorenz et al (2012) 56 Metcalf & Pammer (2014) 33 Pawlikowski & Brand (2011) 57 Qi et al (2015) 58 Sun et al (2009)…”
Section: Age and Symptom Durationmentioning
confidence: 99%
“…Yet, a growing number of studies have been produced in this field in the last two decades (Andreassen et al, 2016). Indeed, several research projects have been exploring VG addiction from a behavioral, emotional, brain circuits and genetic perspectives (Griffiths et al, 2012;Dong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been noted that IGD subjects are associated with failures in controlling the desire for playing online games (Lin et al, 2015a). Numerous imaging studies have found impaired executive control ability in IGD subjects (Dong and Zhou, 2010; Dong et al, 2010, 2011b, 2012a, 2014b, 2015, 2017b; Dong and Potenza, 2014; Weinstein and Lejoyeux, 2015; Wang L. et al, 2016a,b; Wang Y. et al, 2016b; Weinstein et al, 2017), yet, the direct evidence for the impaired executive control ability in inhibiting craving for game-playing in the context of online gaming cues are still lacking (Ko et al, 2008, 2013; Han et al, 2010; Sun et al, 2012). Thus, the present study filled in the gap.…”
Section: Introductionmentioning
confidence: 99%